Tissue plasminogen activator (tPA) treatment for COVID 19 associated respiratory failure: A case Series (Bangladesh Critical Care Journal, 2022)
The global pandemic of COVID-19 has oversaturated the medical care facilities with a large proportion of patient associated with acute respiratory distress syndrome (ARDS). ARDS in patients with COVID-19 is associated with high incidence of pulmonary embolism, pulmonary hypertension and microthrombotic complications. Although heparin is frequently used to treat thrombotic pathology COVID-19, pulmonary embolism is still observed in severe cases. Pathology reports consistently demonstrate diffuse pulmonary microthrombi on autopsy, consistent with vascular occlusive etiology of respiratory failure rather than the more classic finding in ARDS. Pulmonary microthrombi induced respiratory failure is very difficult to prove because the patients are so critically ill that transfer to CT suit to do CT pulmonary angiogram (CTPA) often become unsafe for the patients. Moreover, performing V/Q scan is increasingly difficult in these settings. Here we report a case series of 10 patients with severe COVID-19 associated respiratory failure who were treated with tissue plasminogen activator (tPA).Bangladesh Crit Care J March 2022; 10 (1): 62-67